Argentina : First Review Under the Extended Arrangement Under the Extended Fund Facility, Request for Modification of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Argentina. - International Monetary Fund. Western Hemisphere Dept.. (Washington, D.C. : International Monetary Fund, 2022)
First Review under the Extended Arrangement under the Extended Fund Facility, Request for Modification of Performance Criteria, and Financing Assurances Review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Argentina